Epithelial mitochondrial fission-mediated PANoptosis is crucial for ulcerative colitis and its inhibition by saquinavir through Drp1 - Zhiming Ye; Mingxia Deng; Yang Yang; Yuanming Song; Liangkun Weng; Wanchen Qi; Ping Ding; Yihang Huang; Can Yu; Yan Wang; Yixing Wu; Yan Zhang; et al. (Pharmacological Research)
Ulcerative colitis (UC) is characterized by increased cell death in intestinal epithelial cell (IEC), which compromises gut barrier function and activates inflammation. Aberrant mitochondrial dynamics have been implicated in various forms of cell death, but it is currently unclear if they play a role in IEC death and colitis pathogenesis. This study aims to investigate the contribution of aberrant mitochondrial dynamics to colitis progression using cellular models, animal models, and clinical samples. The results revealed that IEC in mice with Dextran sulfate sodium salt (DSS)-induced colitis exhibited dynamin-related protein 1 (Drp1)-mediated mitochondrial fission and Z-DNA binding protein 1 (ZBP1)-dependent PANoptosis, which is a combination of apoptosis, necroptosis, and pyroptosis. However, these processes and the pathogenesis of DSS-induced colitis were significantly attenuated in IEC-specific Drp1 heterozygous knockout mice. Importantly, ZBP1-PANoptosis and Drp1-mediated mitochondrial fission were observed in IEC of UC patients, exhibiting a positive correlation with disease severity. Mechanistically, hyperactivated mitochondrial fission induced mitochondrial reactive oxygen species production leading to PANoptosis through ZBP1 sulfenylation at Cys327 independently of its Zα domain. Saquinavir, an FDA-approved drug identified through in-silico screening alongside in vivo and in vitro experiments, inhibits mitochondrial fission thereby enhancing therapeutic efficacy in mice with colitis.